Media Relations in the PR Structure of the Judiciary - Vladimirovna Tretyakova, Olga; Nikolaevna Ivanishcheva, Olga; Vladimirovna Gushchina, Anna; Vladimirovna Tretiakovich, Ekaterina; Gennadievna Piksendeeva, Viktoria (International Journal of Engineering and Technology, 2018)
The article analyzes the liaison between judges and journalists as part of the information policy of the judiciary. It is shown herein that the restriction of access to judicial information, the shortcomings in the operation of the communication and information structures of the courts hinder the maintenance of the authority of justice in society. It is proved that the press service is responsible for public relations and media relations. As a result of this approach, the press services created by the courts are unable to participate efficiently in the interaction of the media and the judiciary, and the contacts between journalists and judges are minimized. The data of surveys of judges, journalists and the population of the Arkhangelsk Region are presented with the purpose to reveal if information about judicial proceedings is in demand in society and how open the judiciary is. It is shown that the majority of judges of district and city courts consider that the information on the operation of courts is in demand by society to a sufficient degree. However, at the same time, journalists face the problems of access to information, although the population considers the information on the operation of the judiciary in demand.Â Â Â